PERBANDINGAN PEMBELAJARAN KONVESIONAL DANPEMBELAJARAN MODIFIKASI BELADIRI TERHADAPPENINGKATAN KEBUGARAN JASMANI SISWA SMP 3 KOTA GORONTALO - Hadjarati, Hartono (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2014)
AbstractThis research aimed in improving thephysical fitness status through the martial art modification approach. The researchwas aquantitative study with an experimental approach. The experimental design was Complete Randomized FactorialDesign 2x1, the entire population of the seventh grade students were divided into 2 groups, ie groups of conventionallearning and groups of martial art modification learning. Based on the results of data analysis and discussion of theresults, it can be concluded that the status of physical fitness of the students from SMP 3 Gorontalo in the groupsof students with conventional learning and in the groups of martial art modification learning shows that there is nosignificant contrast between the two learning, so between the two learning approaches give the improvement ofphysical fitness for the students effectively and appropriately used for the learning process which is particularly forPhysical Education.Keywords: Physical Fitness, Learning, Martial Art ModificationsAbstrakPenelitian ini bertujuan untuk meningkatkan status kebugaran jasmani dengan melalui pendekatan pembelajaranmodifikasi beladiri. Penelitian ini adalah penelitian kuantitatif dengan pendekatan eksperimental. Desain eksperimentalyang digunakan adalah Complete Randomized Factorial Design 2 x 1, populasi seluruh siswa-siswa kelas 7 yangdibagi 2 kelompok sampel, yaitu kelompok pembelajaran konvensional dan kelompok pembelajaran modifikasibeladiri. Berdasarkan hasil analisis data dan pembahasan hasil penelitian, dapat diambil disimpulkan bahwa statuskebugaran jasmani siswa-siswa SMP 3 Kota Gorontalo kelompok siswa dengan pembelajaran konvensional danpembelajaran modifikasi beladiri tidak terdapat perbandingan yang signifikan antara kedua pembelajaran tersebut,sehingga antara dua pembelajaran untuk peningkatan kebugaran jasmani siswa-siswa efektif dan tepat digunakanuntuk proses pembelajaran yang ada khususnya PJOK.Kata Kunci: Kebugaran Jasmani, Pembelajaran, Modifikasi Beladiri